Clinical features, sex differences and outcomes of myocardial infarction with nonobstructive coronary arteries: a registry analysis. Issue 1 (January 2021) - Jung, Richard G.; Parlow, Simon; Simard, Trevor; Chen, Christopher; Ghataura, Harshpreet; Kishore, Aditya; Perera, Aravinda; Moreland, Rob; Hughes, Ian; Tavella, Rosanna; Hibbert, Benjamin; Beltrame, John; et al.
Abstract : Introduction: Clinical characteristics and outcomes of patients diagnosed with myocardial infarction (MI) with nonobstructive coronary arteries (MINOCA) remain largely unknown. Furthermore, we do not yet understand if women with MINOCA have worse outcomes similar to what has historically been observed with MI. The aims of the current study were to evaluate the (1) incidence of MINOCA in patients presenting with MI, (2) compare in-hospital outcomes of MINOCA and obstructive atherosclerotic coronary artery disease MI (OACD-MI), and (3) comparison of in-hospital clinical outcomes of patients with MINOCA stratified by sex. Methods and results: In this observational study, we combined data from two large university hospitals from Canada and Australia. Clinical characteristics and in-hospital outcomes of MINOCA and OACD-MI were analyzed by matching these patients in a 1:1 ratio after selecting patients with OACD-MI by systematic random sampling. Clinical characteristics associated with MINOCA were identified through multivariate logistic regression. Primary outcome of interest was net adverse cardiovascular events (NACE) defined as death, heart failure, stroke, and major bleeding. The incidence rate of MINOCA was 9.5%. Women, absence of traditional cardiac risk factors, and absence of ST-deviations on ECG were associated with diagnosis of MINOCA on angiography. NACE ( P  = 0.0001), death ( P  = 0.019), stroke ( P  = 0.002), and heart failure ( P  = 0.001) were significantly lower in patients with MINOCA. Subgroup analysis of women and men diagnosed with MINOCA revealed similar in-hospital outcomes. Conclusion: The incidence of MINOCA was 9.5%. Compared to OACD-MI, patients with MINOCA have less cardiac risk factors. In-hospital outcomes of patients diagnosed with MINOCA were better than OACD-MI.